KRITIK NU TERHADAP SISTEM PENYELENGGARAAN PEMILIHAN KEPALA DAERAH - Asrizal (Millah: Journal of Religious Studies, 2017)
Local elections in Indonesia has always been a public concern. Various cases and long problem continues to occur in the local election process. So it makes the people of Indonesia moved to resolve the problems that exist. Likewise with the Nahdlatul Ulama. NU in Bahtsul Masail noted two problems; (1) not yet the change in voter behavior that impact on the flourishing practice of money politics and transactional politics. (2) Current local elections show the configuration of the political candidates varies greatly from one area to another area prone to conflict and dispute over the number of local elections. In this case the NU forward two plans: (1) Formed a special team tasked with monitoring the implementation of the elections and maintain institutional neutrality of the Nahdlatul Ulama in the implementation of election. (2) PBNU together with other components of society, particularly religious organizations, to continue to carry out propaganda aimed at providing political education in order to exercise the right to choose rightly, responsible and intelligent, so they can elect regional head candidate who has the capacity and integrity of the good.